(untitled) (Journal of the College of Basic Education, 2022)
In this work crud alcoholic extract of Lavendula multifida and Melissa officinalis were prepared .effects of different concentrations of these extract on the activity of MAO ,and AchE were studied in normal human sera and in mice brain . Kinetic constant (Kmap,Vmap,and type of inhibition) were calculated for the enzymes with extract of herbal . The results confirm that alcoholic extract of Melissa acted as competitive inhibitor with the two enzymes while alcoholic extract of lavender acted as uncompetitive inhibitor with the above enzymes .and there are significant differences in enzymes activity in mice before and after herbal dose. The aim of this study to show the effect of lavender and mellisa on the activity of MAO and AChE and using these herbal in treatment of any disease lead to increase these two enzymes .